Oral Care With Evidence of Nausea and Vomiting In Breast Cancer Patients Treating Chemotherapy - Dwiyanti Purbasari; Ahmad Syaripudin; Yanti Susan (Eduvest - Journal of Universal Studies, 2022)
This study was to determine the relationship between oral care and the incidence of nausea and vomiting in breast cancer patients undergoing chemotherapy. This research method uses descriptive correlation by using a cross sectional approach. The sample of this study was breast cancer patients who underwent chemotherapy as many as 34 respondents using accidental sampling technique. The results of the univariate analysis of this study with oral care in the poor category as many as 29 respondents (82.9%) and nausea and vomiting in the poor category as many as 27 respondents (77.1%) in breast cancer patients undergoing chemotherapy. The results of this study found a relationship between oral care and nausea and vomiting in breast cancer patients undergoing chemotherapy with a value (p = 0.000 < = 0.05). In conclusion, the treatment is able to monitor the management of nausea and vomiting due to chemotherapy, the patient's response before, during and after chemotherapy, as well as assessing the effectiveness of oral care actions carried out by patients and their families